Governing Integrated Water Resources Management: Mutual Learning and Policy Transfer - Fritsch, Oliver (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Integrated Water Resources Management (IWRM) has become a global paradigm for the governance of surface, coastal and groundwaters. This Special Issue contains twelve articles related to the transfer of IWRM policy principles. The articles explore three dimensions of transfer-causes, processes, outcomes-and offer a theoretically inspiring, methodologically rich and geographically diverse engagement with IWRM policy transfer around the globe. As such, they can also productively inform a future research agenda on the 'dimensional' aspects of IWRM governance. Regarding the causes, the contributions apply, criticise, extend or revise existing approaches to policy transfer in a water governance context, asking why countries adopt IWRM principles and what mechanisms are in place to understand the adoption of these principles in regional or national contexts. When it comes to processes, articles in this Special Issue unpack the process of policy transfer and implementation and explore how IWRM principles travel across borders, levels and scales. Finally, this set of papers looks into the outcomes of IWRM policy transfer and asks what impact IWRM principles, once implemented, gave on domestic water governance, water quality and water supply, and how effective IWRM is at addressing critical water issues in specific countries.